Pengaruh Stres Kerja dan Lingkungan Kerja terhadap Produktivitas Karyawan pada PT Arisuadi Sejahtera Abadi - Fathia Rizqi Ananda; Ni Nyoman Sawitri; Adi Wibowo Noor Fikri; Dewi Puspaningtyas Faeni; Indah Rizki Maulia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of work stress and the work environment on employee productivity at PT Arisuadi Sejahtera Abadi. The research method used is quantitative research, which means research used to examine certain populations and samples, data collection using research instruments, quantitative or statistical data analysis, with the aim of testing predetermined hypotheses. The sampling technique used was saturated sampling technique or the entire population was sampled. The population in this study was 53 respondents. Data analysis uses Smart PLS 3.0 software and hypothesis testing, namely the t test and F test. Based on the results of the path coefficient hypothesis test, there are P-values ​​of 0.000 or <0.05 and the work stress t-statistics value is 3,588 or > 1.96 , it is stated that there is a significant influence between work stress variables on employee productivity. Based on the results of the path coefficient hypothesis test, there are P-values ​​of 0.000 or <0.05 and the work environment t-statistics value has a value of 5,468 or > 1.96, so it is stated that there is a significant influence between work environment variables on employee productivity